Analysis of Tax Revenue From Acquisition of Land and Building Rights at The Regional Revenue Agency in Majene District - Haq, Nursyam Arifa; Tikollah, M. Ridwan; Afiah, Nur (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This research aims to determine the contribution of BPHTB revenue to regional income of Majene Regency, the effectiveness of BPHTB revenue to regional income of Majene Regency, and the potential of BPHTB revenue to regional income of Majene Regency. The variable in this research is tax receipts for the acquisition of land and building rights. The population in this research is the Budget Realization Report (LRA), especially the targets and realization of BPHTB taxes, targets and realization of PAD and regional taxes originating from BAPENDA Majene Regency. The sample in this research was taken from the 2020-2022 Regional Revenue Realization Report with a focus on targets and the amount of realized tax revenue from Land and Building Rights Acquisition Tax from Majene Regency BAPENDA staff. The data in this research was collected through interviews and documentation using interactive model data analysis techniques. The results of this research show that the level of contribution of BPHTB tax revenues to PAD revenues is still very less than in 2020-2022 with an average of 1.69%, while the level of contribution of BPHTB tax revenues to regional tax revenues is still less than in 2020-2022 with an average of 15 .79%. The effectiveness of BPHTB tax revenue is still less effective, as evidenced by the average result of 75.29% from 2020-2022. BPHTB's potential tax revenue can be seen from the number of taxpayers paying zero tax in 2020-2022. From the results of the analysis that has been carried out, it appears that the potential amount of BPHTB tax revenue in 2022 is IDR 62,690,500 from 196 taxpayers.